2000
DOI: 10.1080/07315724.2000.10718909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Purine Intake on Uric Acid Excretion in Infants Fed Soy Infant Formulas

Abstract: These data indicate that healthy infants can digest RNA and subsequently absorb the liberated purine ribonucleotides as determined by urinary uric acid concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…No statistically significant effect of their increased intake was observed in the incidence of gout in a large survey study 12. However, their effect on SU levels has been previously confirmed in rats or humans by several authors 13–15. Previous studies have demonstrated that a diet rich in purines causes a SU increase of approximately 59–118 µmol L −1 and, conversely, a purine‐free diet lowered SU by 59–118 µmol L −1 16.…”
Section: Discussionmentioning
confidence: 93%
“…No statistically significant effect of their increased intake was observed in the incidence of gout in a large survey study 12. However, their effect on SU levels has been previously confirmed in rats or humans by several authors 13–15. Previous studies have demonstrated that a diet rich in purines causes a SU increase of approximately 59–118 µmol L −1 and, conversely, a purine‐free diet lowered SU by 59–118 µmol L −1 16.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we have confidence that the interpretation of the age-related differences here are not likely to be due to differential collection methods. Individual serum UA levels increase after the consumption of purine-rich proteins and fructose (Choi et al, 2005;Choi, Ford, Gao, & Choi, 2008;Viazzi, Genovesi, Ambruzzi, & Giussani, 2015), and decreases with the consumption of dairy in adults (Choi et al, 2005) and breast milk in infants (Kuchan, Ostrom, Smith, & Hu, 2000). Given the strong association between serum and salivary UA levels, it is possible that sUA levels are also influenced by diet.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Indirect evidence has recently suggested that the infant is capable of digesting RNA and absorbing the resulting purine ribonucleotides (16). Milk formulas in the United States and other countries are currently supplemented with free nucleotides up to the TPAN levels of human milk, but they do not include RNA as an ingredient despite the recognized presence of RNA in human milk (5).…”
mentioning
confidence: 99%